IMPLEMENTASI TENTANG DISIPLIN PEGAWAI ASN DI UPT DINAS PEKERJAAN UMUM WILAYAH IV KABUPATEN SUKABUMI - Deni Fauzi (STISIP Widyapuri Mandiri, 2023)
This study aims to determine the implementation of employee discipline at UPT Public Works Service Region IV Sukabumi Regency, through the George Edward III theoretical approach model. The research method used is a qualitative research method with a descriptive approach. The selection of informants used the Non-Probability Sampling technique with Purposive Sampling and Snowball Sampling methods. The subjects of this study were 6 (seven) people, namely the UPT Head (1 person), ASN employees (2 people), Non ASN employees (2 people) and 1 community member around the UPT Public Works Service Region IV Sukabumi Regency office. Data collection techniques were carried out by means of observation, interviews and documentation. Then the data analysis carried out included data reduction, data presentation, and data validation using data triangulation techniques. The results obtained in this study are that communication, resources, and attitudes or dispositions in the implementation of ASN employee discipline at UPT Public Works Service Region IV Sukabumi Regency have not been carried out properly, while the bureaucratic structure has been structured and its application is in accordance with SOP.